1964
DOI: 10.3181/00379727-115-28996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc on Cancerogenesis by Cadmium.

Abstract: Concomitant nephrectomy. However, the endogenous parathyroid stimulation produced by nephrectomy also resulted in an increase in bound hydroxyproline which is detectable only after hydrolysis of the lavage fluid or pIasma. The results indicate that hydroxyproline levels in plasma and lavage fluid are parathyroid-dependent and can be correlated with calcium removal under the conditions of parathyroidectomy and/or nephrectomy. These studies further suggest that the breakdown of bone under the influence of parath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1966
1966
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…Fourteen rats were observed for a period of one year but no neoplastic changes were reported. On the other hand, cadmium metal (Heath and Daniel, 1964), cadmium sulphate (Haddow et al, 1964;Gunn et al, 1964), cadmium sulphide and cadmium oxide have given rise to malignant tumours at the site of subcutaneous or intramuscular injection in the rat. In addition, interstitial cell tumours of the testis have followed subcutaneous injection of cadmium sulphate ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen rats were observed for a period of one year but no neoplastic changes were reported. On the other hand, cadmium metal (Heath and Daniel, 1964), cadmium sulphate (Haddow et al, 1964;Gunn et al, 1964), cadmium sulphide and cadmium oxide have given rise to malignant tumours at the site of subcutaneous or intramuscular injection in the rat. In addition, interstitial cell tumours of the testis have followed subcutaneous injection of cadmium sulphate ).…”
Section: Discussionmentioning
confidence: 99%
“…Following this observation similar results were obtained in a group of rats given repeated injections of a soluble cadmium salt in the form of cadmium sulphate. (Haddow, Roe, Dukes and Mitchley, 1964;Roe, Dukes, Cameron, Pugh and Mitchley, 1964) Sarcomata at the injection site and testicular tumours were later reported following the single subcutaneous injection of a relatively small dose of cadmium chloride, another soluble compound (Gunn, Gould and Anderson, 1964). Finely divided cadmium metal suspended in serum and injected into the thigh muscle of the rat led to the production of rhabdomyosarcoma and fibrosarcoma in an experiment given in a preliminary report by Heath, Daniel, Dingle and Webb (1962), and described in detail by Heath and Daniel (1964).…”
mentioning
confidence: 99%
“…Exposure of the workers to other pollutants may also influence carcinogenicity. For example, it has been shown that simultaneous subcutaneous injection of cadmium and zinc salts inhibits or prevents the carcinogenic effect on the testes and injection sites of cadmium chloride when administered alone (26,27). It is unknown whether this phenomenon would also be true for inhalational exposure.…”
Section: Extrapolation Of Pulmonary Effects Of Cadmium From Animals Tmentioning
confidence: 99%
“…Thus, protooncogene induction correlates with the metal specificity of the orphan receptor as well as reversible manipulation of orphan receptor responsiveness by varying the Zn2+ level of the culture medium. Notably Zn2+ markedly decreases tumor induction by Cd2+ (96)(97)(98). Further work is needed to evaluate the roles of protein phosphorylation and the putative orphan receptor in protooncogene induction and mitogenic stimulation by divalent metals.…”
Section: Protooncogene Induction By Cadmiummentioning
confidence: 99%